Caracterización del proceso de transformación primaria de la madera en la empresa Raices Gaddaffy SCRL. Iquitos, Loreto – 2023 - Villacorta Perez, Juana Luisa (2024)
The present study was carried out in Raíces Gaddaffy SCR company, located at 2109 La Marina Avenue, Punchana District, in order to characterize the entire primary transformation process of wood in Raíces Gaddaffy SCR company. From the obtained results, it can be seen that the company buys raw material from third parties, it does not have forestry concessions or any other type of use for its supply. The company pays river transport services to private companies to move its wood from different basins in the Amazon. The misaligment of the pieces or tables is common in the sawmill due to the por condition of the main saw and saw carriage. The controlled logs in the sawmill had an average of 0.87 m in diameter and 4m in length with an average volumen of 0.953 m³. The pieces obtained after the sawing process are subjected to a preventive preservation process, to ensure the quality of the pieces for a very short time. The drying process is carried out basically for 1 inch of thickness with an average duration of 6 to 7 days. The classification of the wood after drying yields of 55% in one and two faces, 15% in common N° 1,17% in common N°2,8% in common N° 3, and 5% waste. The average Price of cumala sawn timber for export per board foot is S/. 4.11 in its different qualities and S/. 2.35 in the national market.